2018
DOI: 10.1111/petr.13316
|View full text |Cite
|
Sign up to set email alerts
|

Healthy hearts in pediatric heart transplant patients with an exercise and diet intervention via live video conferencing—Design and rationale

Abstract: Background: Pediatric heart transplant (PedHtx) patients have increased cardiovascular risk profiles that affect their long-term outcomes and quality of life. We designed a 12-to 16-week diet and exercise intervention delivered via live video conferencing to improve cardiovascular health. Our methodology and baseline assessment of the first 13 enrolled patients are reported. Methods: Inclusion criteria are as follows: (a) 8-19 years old; (b) heart transplant >12 months; (c) ability to fast overnight; (d) cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
0
9
0
1
Order By: Relevance
“…Previous studies examining individual CVH metrics among pediatric HT recipients have been somewhat inconsistent, with some but not all suggesting worse levels of CVH metrics among HT recipients compared with the general population. Suboptimal nutrition and a sedentary lifestyle in combination with immunosuppressants and steroid medication are thought to be contributory to worse CVH metrics after HT (3,8,29,31). Several studies suggested increased risks of obesity, dyslipidemia and a higher incidence of type 2 diabetes post-HT (8,13,(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies examining individual CVH metrics among pediatric HT recipients have been somewhat inconsistent, with some but not all suggesting worse levels of CVH metrics among HT recipients compared with the general population. Suboptimal nutrition and a sedentary lifestyle in combination with immunosuppressants and steroid medication are thought to be contributory to worse CVH metrics after HT (3,8,29,31). Several studies suggested increased risks of obesity, dyslipidemia and a higher incidence of type 2 diabetes post-HT (8,13,(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 7894 records were excluded at the title and abstract screening stage, and 97 full text records were assessed for eligibility ( Figure 1 ). A total of 84 of the 97 full text records were excluded for the following reasons: 26 did not measure smoking, nutrition, alcohol consumption, physical activity, and obesity outcomes; 23 did not use any form of video counseling intervention; 19 involved group video counseling and not individual video counseling [ 37 - 54 ]; 3 were protocol papers [ 55 - 57 ]; 8 were not randomized studies [ 58 - 65 ]; 2 studies were ongoing [ 32 , 66 ]; 1 was a conference abstract [ 67 ]; and 2 studies described a multicomponent intervention, and it was not possible to isolate the effect of real-time video counseling [ 68 , 69 ]. The remaining 13 eligible studies were included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 7894 records were excluded at the title and abstract screening stage, and 97 full text records were assessed for eligibility (Figure 1). A total of 84 of the 97 full text records were excluded for the following reasons: 26 did not measure smoking, nutrition, alcohol consumption, physical activity, and obesity outcomes; 23 did not use any form of video counseling intervention; 19 involved group video counseling and not individual video counseling [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]; 3 were protocol papers [55][56][57]; 8 were not randomized studies [58][59][60][61][62][63][64][65]; 2 studies were ongoing [32,66]; 1 was a conference abstract [67]; and 2 studies described a multicomponent intervention, and it was not possible to isolate the effect of real-time video counseling [68,69]. The remaining 13 eligible studies were included in the review.…”
Section: Resultsmentioning
confidence: 99%